Empowering Women Leaders for Work-Integrated e-Learning: Social Changes and Persistent Challenges - Wong, Amy; Sixl-Daniell, Karin (International Journal of Advanced Corporate Learning (iJAC), 2020)
Information technology is increasingly being adopted within various sectors, especially in education. This study examines the effects of a work-integrated e-learning program for women leaders offered by a fully online institution. Data was collected from 61 respondents via an online discussion board forum. The findings showed that integration of technology-enhanced learning into the workplace for purposes of training and development can bring about a variety of social changes at the individual, group, and organizational levels. The findings highlight important insights for the design and delivery of fully online training and development programs that can bring about social change, taking into consideration the persistent challenges faced by women leaders. Further discussion and implications are provided.